The violence of norms: resisting repertoires of gender violence in post-conflict Colombia. Issue 2 (17th February 2022) - Bates, Jennifer
ABSTRACT: Feminist scholarship on gender violence in Latin America has elucidated its ubiquity and deep entrenchment within many societies, from the colonial encounter until the present day. As such, it remains important to enquire into the relationship between sociocultural norms and gender violence: how norms enable and legitimate gender violence, and how these norms can be reconfigured to resist gender violence. This article draws on Judith Butler's work on normative violence to explore how norms enabled, legitimated and obscured the distinct repertoires of gender violence in Colombian civilian society and left-wing rebel group the Revolutionary Armed Forces of Colombia (FARC). Butler's theorization on how norms can be challenged, both through different gender performances and the revision of criteria of gender intelligibility, is then extended to understanding the emergence of resistance to gender violence in The Common Alternative Revolutionary Force, the political party which the FARC transitioned into in 2017.